Determination of Glucosamine in Human Plasma by High-Performance Liquid Chromatography-Atmospheric Pressure Chemical Ionization Source-Tandem Mass Spectrometry. (15th June 2011) - Zhou, Xingchen; Cheng, Zeneng; Ran, Liling; Guo, Xin; Liu, Zhi; Yu, Peng
Abstract : A sensitive, specific, and rapid high-performance liquid chromatography-atmospheric pressure chemical ionization source-tandem mass spectrometry (HPLC-APCI-MS/MS) method for the determination of glucosamine in human plasma was developed and validated. Plasma samples were processed by protein precipitation with dehydrated ethanol, and the chromatographic separation was performed on an Agilent XDB-C18 column with a mobile phase of methanol—0.2% formic acid solution (70 : 30, v/v). Mass spectrometric quantification was carried out in the multiple reaction monitoring (MRM) mode, monitoring ion transitions of m/z 180.1 to m/z 162.1 with collision energy (CE) of 2 eV for glucosamine and m/z 181.1 to m/z 163.1 with CE of 2 eV for the internal standard (IS) in positive ion mode. The linear calibration curves covered a concentration range of 53.27–3409 ng/mL with a lower limit of quantification (LLOQ) of 53.27 ng/mL. The extraction recovery of glucosamine was greater than 101.7%. The intra- and interday precisions for glucosamine were less than 10%, and the accuracies were between 93.7% and 102.6%, determined from quality control (QC) samples of three representative concentrations. The method has been successfully applied to determining the plasma concentration of glucosamine in a clinical pharmacokinetic study involving 20 healthy Chinese male volunteers.